2012
DOI: 10.3190/jgeosci.107
|View full text |Cite
|
Sign up to set email alerts
|

Marrucciite, a rare Hg-sulfosalt from the Gelnica ore deposit (Slovak Republic), and its comparison with the type occurrence at Buca della Vena mine (Italy)

Abstract: The rare Hg-sulfosalt, marrucciite, with ideal formula Hg 3 Pb 16 Sb 18 S 46 , was found in the Gelnica ore deposit (Spišsko-Gemerské Rudohorie Mts., Slovak Republic). It occurs as acicular crystals up to 0.5 mm in length and fine-grained aggregates up to 1 mm in quartz (+siderite/dolomite) gangue in association with other sulfosalts (zinkenite, scainiite, boulangerite, chalcostibite, bournonite) and cinnabar. It is opaque, dark steel grey to greyish black, sometimes tarnished to a bronze-brown tint, has a dar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…It might be caused by the acicular shape of hodrušite crystals. Similar situation was also described for another fibrous sulphosaltmarrucciite (Sejkora et al 2011). The refined unit-cell parameters (Tab.…”
Section: Minerals Of the Cuprobismutite Homologous Series (Hodrušitesupporting
confidence: 80%
“…It might be caused by the acicular shape of hodrušite crystals. Similar situation was also described for another fibrous sulphosaltmarrucciite (Sejkora et al 2011). The refined unit-cell parameters (Tab.…”
Section: Minerals Of the Cuprobismutite Homologous Series (Hodrušitesupporting
confidence: 80%
“…It might be caused by the acicular shape of grumiplucite crystals (Toraya and Marumo 1981). Similar situation was also described for other fibrous sulfosalts -marrucciite (Sejkora et al 2011), hodrušite or antimonselite (Škácha et al 2015). The refined unit-cell parameters of both types of grumiplucite from Rudňany (Tab.…”
Section: Grumiplucitementioning
confidence: 63%
“…Other Bi sulphosalts like cosalite (Bernard 1964, Háber 1980), galenobismutite (Antal 1991, Pršek 2008, jaskólskiite (Pršek, Biroň 2007), nuffieldite (Pršek et al 2006) or wittichenite (Háber 1978;Kozub et al 2011) are rare. Chalcostibite is infrequent too (Sejkora et al 2011;Mikuš et al 2018). Unusual assemblage of Ag-Bi sulphosalts (matildite, gustavite and benjaminite) was recently described from Kobaltová vein near Medzev by Mikuš et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…The most common Pb sulphosalts at the siderite-type veins are bournonite, jamesonite and boulangerite (e.g. Zimányi 1914;Novák 1962;Trdlička 1967;Kupčík et al 1969;Háber 1980;Miškovic 1990;Pršek, Biroň 2007;Pršek, Peterec 2008;Sejkora et al 2011;Mikuš et al 2018Mikuš et al , 2019 man 1994) or zinkenite and scainiite (Sejkora et al 2011) are scarce. Rare Hg sulphosalts, marruccite (Sejkora et al 2011) and grumiplucite (Števko et al 2015) were also recently identified.…”
Section: Introductionmentioning
confidence: 99%